Venezuelan immigration, border and interculturality: an analysis of public schools’ educators experiences in Boa Vista (Roraima) - Generali, Sabrina (2024)
This article aims to analyze the experiences of educators from public schools of Boa Vista (RR), related to the presence of immigrant diversity of Venezuelan children, and the possibilities of including intercultural practices in school spaces. The theoretical framework covers the concepts of borders, interculturality and immigration. The methodology, of qualitative assumptions, included interviews, exploratory, bibliographical, and documental research. The empirical analysis is developed based on three dimensions of educators’ experiences related to interculturality: the educators’ perspective of the relation with the border, Boa Vista schools as spaces of migratory diversity and the absence of public policies aimed at interculturality. As results, we observed possibilities and limits for the development of intercultural educational practices in the border context, the absence of intercultural projects and policies in schools and an understanding of the temporary nature of the migratory presence.